Hypoxic Living and Exercise Training Alter Adipose Tissue Leptin/Leptin Receptor in Rats - Lu, Yingli; Feng, Lianshi; Xie, Minhao; Zhang, Li; Xu, Jianfang; He, Zihong; You, Tongjian (Frontiers in Physiology, 2016)
Background: Hypobaric hypoxia results in weight loss in obese individuals, and exercise training is advocated for the treatment of obesity and its related metabolic dysfunctions. The purpose of this study was to investigate the effects of hypoxic living and exercise training on obesity and adipose tissue leptin/leptin receptor in dietary-induced obese rats. Methods: One hundred and thirty high-fat diet fed Sprague-Dawley rats were assigned into one of the following groups (n=10 each): control, sedentary hypoxic living for 1 to 4 weeks (SH1, SH2, SH3, and SH4), living and exercise training in normoxic conditions for 1 to 4 weeks (TN1, TN2, TN3, and TN4), and living and exercise training in hypoxic conditions for 1 to 4 weeks (TN1, TN2, TN3, and TN4). Epididymal adipose tissue expression levels of leptin and leptin receptor were determined. Results: Compared to hypoxic living and living and exercise training in normoxic conditions, living and exercise training in hypoxic conditions for 3-4 weeks resulted in lower Lee index (P<0.05 to P<0.01), and higher expression of leptin and leptin receptor (P<0.05 to P<0.01) in adipose tissue. Conclusion: In a rodent model of altitude training, living and exercise training in hypoxic conditions resulted in greater alterations in obesity and adipose tissue leptin/leptin receptor than hypoxic living alone and living and exercise training in normoxic conditions.